2018
DOI: 10.24908/pceea.v0i0.12981
|View full text |Cite
|
Sign up to set email alerts
|

Using an Academic Plan Model to Analyze Canadian Engineering Leadership Curriculum

Abstract: This paper analyzes engineering leadership curriculum in Canadian universities. Using an adapted framework for curriculum development, we analyze key documents for six engineering leadership programs in six different universities. Findings show a wide range of purposes, content and sequencing, with a common core of instructional processes and resources. We explore how accreditation, labour markets, internal resources and relationships with business schools shape curriculum decisions. Future work will explore d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
10
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
3

Relationship

2
7

Authors

Journals

citations
Cited by 10 publications
(10 citation statements)
references
References 13 publications
(12 reference statements)
0
10
0
Order By: Relevance
“…Traits of effective engineer leaders include several skills typically described by the process of project management (Engineering Management Institute, 2016). Utilizing the model differentiating academic plans from key influences from Lattuca and Stark (2009), Klassen and Donald (2018) developed a curriculum development framework to assess leadership offerings in engineering schools. A comparative study of six programs revealed that lecture remained the most prevalent teaching modality.…”
Section: The Case For Leadership Curriculamentioning
confidence: 99%
“…Traits of effective engineer leaders include several skills typically described by the process of project management (Engineering Management Institute, 2016). Utilizing the model differentiating academic plans from key influences from Lattuca and Stark (2009), Klassen and Donald (2018) developed a curriculum development framework to assess leadership offerings in engineering schools. A comparative study of six programs revealed that lecture remained the most prevalent teaching modality.…”
Section: The Case For Leadership Curriculamentioning
confidence: 99%
“…Klassen and Donald [17] used the academic plan model to compare engineering leadership curricula in Canadian universities. Their focus was on specific courses and cocurricular programs whereas we recognized that some engineering science units in the consortium are entire schools with multiple departments, programs, and specialisations.…”
Section: The Academic Plan Modelmentioning
confidence: 99%
“…Case Studies, Real-World Labs, Service Learning [26], [32], [15], [17], [28], [34], [31], [35] Course Delivery [26], [27], [29], [36], [37], [30], [33], [38], [39] Assessment [13], [16], [40], [41], [22], [42], [23], [43], [44] Theory Based or Survey Results [11], [45], [46], [47], [10], [19], [48], [1], [39], [49], [24], [25], [50], [51], [52] Out-of-class activities [53], [54], [55], [56], [57], [58] While there have been many successful interventions that improved student motivation discussed in the CEEA 2010-2018 proceedings, the relevant motivation theory behind each intervention is often missing. Understanding motivation theory may not be necessary ...…”
Section: Type Of Interventionmentioning
confidence: 99%